Pylorus Preserving Pancreatoduodenectomy Versus Whipple Procedure for Adenocarcinoma of The Head of The Pancreas. Issue 3 (1989) - Belli, Lino; Riolo, Franco; Romani, Federico; Baticci, Fabio; Rossetti, Ornella; Puttini, Maurizio
Abstract : Thirty eight patients underwent pancreatoduodenectomy for histologically confirmed adenocarcinoma of the head of the pancreas. Twenty one underwent a pylorus preserving pancreatoduodenectomy and seventeen the classical Whipple procedure. We undertook this retrospective analysis to compare longterm survival following the two different surgical procedures. Patients in the two groups were comparable for preoperative laboratory data, age and pathological staging. Minor and major morbidity was not different between the two groups (33.3% and 35.2% respectively). In the pylorus preservation group a delayed resumption of full oral diet and a consequent prolonged hospital stay has been noted (;21.3 days vs 15.4 days, p<0.05). Mean survival was 21 months in the pylorus preservation group and 17 in the Whipple group. No statistical difference was observed between the two survival curves. According to these data the pylorus preserving pancreatoduodenectomy represents a reasonable option for adenocarcinoma of the head of the pancreas.